Attitudes toward abortion among the Icelandic public - Katrín Sól Þórðardóttir 2000- (2023)
Abortions are very common; about 73 million abortions are performed worldwide each year. In Iceland, there were 962 documented abortions in 2020. Attitude toward abortion is a very important subject because if abortions are illegal or shameful, women might be led to have unsafe abortions. Of all abortions performed worldwide, around 45% are unsafe and can result in hemorrhaging, infections, and death. The current study examined Icelandic individuals' attitudes toward abortion. The study examined the relationship between attitudes towards abortion by gender, age, level of feminism, and if the individual knew someone who had received an abortion. The participants in the study were 489, with 321 females (65.6%), 166 males (33.9%), and two participants who were non-binary or didn't want to answer (0.2%). The age range was 18-77, with a mean age of 32 years. The findings revealed that the people with the most positive attitudes towards abortion were women, those who were younger, and participants who reported a higher level of feminism. Knowing someone who had received an abortion did not relate to abortion attitudes. Keywords: abortion, attitude, gender, age, feminism Þungunarrof eru mjög algeng en um 73 milljónir þungunarrofa eru framkvæmd á ári hverju á heimsvísu. Á Íslandi voru 962 þungunarrof framkvæmd árið 2020. Viðhorf til þungunarrofa eru mjög mikilvæg vegna þess að ef þungunarrof eru ólögleg eða vekja upp skömm þá eru konur oft neyddar til þess að fara í óöruggt og hættulegt þungunarrof sem getur leitt til blæðingar, sýkingar og dauða. Þessi rannsókn skoðar viðhorf Íslendinga til þungunarrofa. Rannsóknin skoðar hvort kyn, aldur, femínismi og hvort einstaklingur þekkir annan sem hefur farið í þungunarrof hafi áhrif á viðhorf hans til þungunarrofa. Þátttakendur rannsóknarinnar voru 489, þar af 321 konur (65,6%) and 166 karlar (33,9%) og tveir voru kynsegin eða vildu ekki svara. Aldur þátttakenda var á bilinu 18 til 77 ára en meðalaldurinn var 32 ára. Niðurstöðurnar leiddu í ljós að konur eru með jákvæðari ...